Le discours de l’ironie dans Maryse<i/i> de Francine Noël - Grzybowska, Anna Maria (Romanica Silesiana)
Maryse, a postmodern novel by Francine Noël, offers an ironic look at the baby boomers’ uncertain axiology. We focus on the multiple levels of irony inherent in the portrait of the characters of the novel. Our analysis of the ironic discourse has two interpretative components. First, we closely examine the dialogue between two characters, lovers, which reflects, as in a mise en abyme, the baby boomers’ generally accepted idea of the couple. Second, we study the ironic discourse of the couple from the social perspective, as seen through Maryse’s sentimental affair, whose personal and professional journey exemplifies the intertextual game found in other French classic novels (Marcel Proust’s À la recherche du temps perdu and Quebecois novels (Gabrielle Roy’s Bonheur d’occasion). Key words: The postmodern novel, the couple, intertextual game, the baby boom generation, the literary portrait of a protagonist, the ironic.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />